Effect of seed borne fungi on seed quality of sunflower (Helianthus annuus) - M. MONICA; B. RAJESWARI; K. KESHAVULU; K.V.S. MEENA KUMARI; M. SURESH; R.D. PRASAD (Seed Research, 2026)
An experiment was conducted to study the effect of Alternaria helianthi on seed quality attributes of sunflower (Helianthus annuus L.) cultivars. Alternaria blight infected seeds were thin, pale black, shrivelled, wrinkled, ill filled and showed discolouration on seed coat. Morden and Local cultivars of Ranga Reddy and Nizamabad districts recorded highest total seed-borne fungi (53 and 55%). The samples of Nalgonda district recorded maximum occurrence of seed-borne fungi (49%), whereas occurrence of A. helianthi was recorded with a range of 2.5-4.5%. Significant differences in seed germination (44-60%) and seed vigour index (470-797) was recorded. The germinabilty was far below the minimum seed certification standard of